1985
DOI: 10.1259/0007-1285-58-696-1183
|View full text |Cite
|
Sign up to set email alerts
|

Scintigraphy and contrast radiography for epiphora

Abstract: During a one-year period 53 patients were referred for the investigation of epiphora. All underwent bilateral dacryoscintigraphy. Following the isotope study the patients had either bilateral or unilateral macrodacryocystography; a total of 66 tear ducts were shown by this procedure. The scintigraphs were more sensitive for obstruction (51/66 systems or 77%) than radiography (33/66 systems or 51%). Normal dacryoscintigraphy was always associated with duct patency on dacryocystography. We have concluded that sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 2 publications
2
9
0
1
Order By: Relevance
“…Similar observations were reported by Rose et al, who compared dacryocystography with scintigraphy and found better sensitivity (77% vs 51%) for scintigraphy. Like syringing, this confirms the non-physiological character of dacryocystography [14]. In line with these observations, Nixon and colleagues concluded that the results of dacryocystography had no relevant influence on the choice of treatment [12].…”
Section: Discussionsupporting
confidence: 52%
“…Similar observations were reported by Rose et al, who compared dacryocystography with scintigraphy and found better sensitivity (77% vs 51%) for scintigraphy. Like syringing, this confirms the non-physiological character of dacryocystography [14]. In line with these observations, Nixon and colleagues concluded that the results of dacryocystography had no relevant influence on the choice of treatment [12].…”
Section: Discussionsupporting
confidence: 52%
“…The sensitivities of lacrimal scintigraphy for detecting obstruction in the symptomatic patients were reported 81.6% by Jabbour et al, 77% by Rose et al and 95% by Wearne et al The sensitivity of 96.3% and specificity of 90.4% were reported by Fard-Esfahani et al [14][15][16][17]. Our study showed high sensitivity (96.3%) and specificity (75.5%) as shown by previous studies mentioned above especially having the "after wash" studies.…”
Section: Discussionsupporting
confidence: 76%
“…Rückschlüsse hinsichtlich der Ursache der Tränenwegsabflussbehinderung sind jedoch im Gegensatz zur Dakryozystographie mittels der DSG nicht möglich [21,44].…”
Section: Radiologische Diagnostikunclassified